1997
DOI: 10.1177/000348949710600603
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Left Main Stem Bronchus Compression

Abstract: There are four major variants of congenital vascular tracheal compression: innominate artery, aberrant subclavian, aorta or aortic arch anomaly, and pulmonary artery sling. These forms of vascular compression typically involve the trachea and/or the right main stem bronchus. We present eight cases of congenital vascular compression involving the left main stem bronchus. These cases represent a poorly understood variant of vascular tracheal compression. This variant represents approximately 10% of our pediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Defining this ''inverted teardrop'' appearance is a controversial diagnostic issue. 16,17 While this appearance is common at entry into the left main stem, closer inspection often reveals the appearance to be due to the curvature of the left main stem without any apparent real reduction in cross-sectional area. While such cases were not included or diagnosed as malacia in this series, the lack of objective measurements necessary to define the normal and observed changes remains a difficulty in assessing minor changes of the left mainstem bronchus.…”
Section: Discussionmentioning
confidence: 99%
“…Defining this ''inverted teardrop'' appearance is a controversial diagnostic issue. 16,17 While this appearance is common at entry into the left main stem, closer inspection often reveals the appearance to be due to the curvature of the left main stem without any apparent real reduction in cross-sectional area. While such cases were not included or diagnosed as malacia in this series, the lack of objective measurements necessary to define the normal and observed changes remains a difficulty in assessing minor changes of the left mainstem bronchus.…”
Section: Discussionmentioning
confidence: 99%
“…Foreign bodies, tracheobronchial or vascular malformations, 46 and intrathoracic airway malacia or stenosis 47 are occasionally found. Compression of the left main stem bronchus was the focus of a recent article, 49 and the most frequent cause seems to be an abnormal prespinal position of the descending aorta, which compresses the bronchus against the left pulmonary artery. 48 Other diagnostic options such as a lateral chest X-ray, computed tomography (CT) scan, and magnetic resonance imaging (MRI), will often not give suf®cient information to obviate endoscopy.…”
Section: Expiratory Wheezing or Rhonchimentioning
confidence: 99%
“…However, previous reports showed that this condition may be also related to compression by congenital anomalies of the thoracic aorta and/or of the pulmonary arteries . In these reports, the etiologic factors found to be most frequently associated with this entity were the anterior displacement of the descending aorta in front to the adjacent vertebral bodies and dilatation of the pulmonary arteries . In children with more severe symptoms, surgical treatment varied according to the complexity of the anatomic anomalies and, when indicated, included posterior aortopexy .…”
Section: Introductionmentioning
confidence: 98%
“…This condition is usually not included in the list of airway anomalies caused by vascular compression because, when not associated with cardiovascular anomalies, it generally attributed to primary localized chondromalacia . However, previous reports showed that this condition may be also related to compression by congenital anomalies of the thoracic aorta and/or of the pulmonary arteries . In these reports, the etiologic factors found to be most frequently associated with this entity were the anterior displacement of the descending aorta in front to the adjacent vertebral bodies and dilatation of the pulmonary arteries .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation